Executive Committee Minutes 2020-10-29 - Academic Senate:::::::::
Agenda – TC of 3:45 for Field Trip Policy – Approved. Minutes of 10/15/2020 – Approved. Chair Report. President Report. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President for Student Affairs Report. Associated Students Report. From EPC: Field Trip Policy – approved for Senate agenda. APARC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Vice President of Administration and Administration Report. Begin planning Faculty Retreat: Topic, format. Senate agenda approved.